2012
DOI: 10.1029/2011wr010759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating interannual water storage changes at watersheds in Illinois based on long‐term soil moisture and groundwater level data

Abstract: [1] The annual water storage changes at 12 watersheds in Illinois are estimated based on the long-term soil moisture and groundwater level observations during . Storage change is usually ignored in mean annual and interannual water balance calculations. However, the interannual variability of storage change can be an important component in annual water balance during dry or wet years. Annual precipitation anomaly is partitioned into annual runoff anomaly, annual evaporation anomaly, and annual storage change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 54 publications
4
134
0
Order By: Relevance
“…Their extended Budyko model (which was also based on Fu, 1981) showed good performance in modeling monthly Q but includes four additional parameters that require extensive calibration. Chen et al (2013) further introduced an approach (referring to Wang, 2012) that is based on replacing P by effective precipitation, which is the difference between P and soil water storage change. This allows the framework to be extended to seasonal timescales but requires explicit knowledge of changes in the soil water storage.…”
Section: Discussionmentioning
confidence: 99%
“…Their extended Budyko model (which was also based on Fu, 1981) showed good performance in modeling monthly Q but includes four additional parameters that require extensive calibration. Chen et al (2013) further introduced an approach (referring to Wang, 2012) that is based on replacing P by effective precipitation, which is the difference between P and soil water storage change. This allows the framework to be extended to seasonal timescales but requires explicit knowledge of changes in the soil water storage.…”
Section: Discussionmentioning
confidence: 99%
“…Istanbulluoglu et al (2012) and Wang et al (2009) showed interannual storage changes can produce a negative correlation between the evapotranspiration ratio and aridity that is counter to the Budyko curve for baseflowdominated basins in the Nebraska Sand Hills. Wang (2012) evaluated inter-annual storage changes for twelve watersheds in Illinois and showed that, on an annual timescale, variability in runoff and storage is larger than evapotranspiration, and accounting for storage can improve the performance of Budyko predictions. Du et al (2016) presented a method for explicitly accounting for storage changes within the Budyko framework and demonstrated that this approach can greatly improve performance in arid regions, or over shorter timescales where the steady-state assumption is not valid.…”
Section: E Condon and R M Maxwell: Systematic Shifts In Budyko mentioning
confidence: 99%
“…However, with both of these approaches the groundwater system is still not directly simulated or observed. Istanbulluoglu et al (2012) and Wang (2012) did use observations of water table depth to directly quantify storage changes and demonstrate the impact of this change within the Budyko framework; but the study areas with this approach were relatively limited (four watersheds for Istanbulluoglu et al, 2012, andtwelve for Wang, 2012). Groundwater observations sufficient to precisely characterize watershed storage changes are difficult to obtain and are not widely available.…”
Section: E Condon and R M Maxwell: Systematic Shifts In Budyko mentioning
confidence: 99%
“…Yokoo et al (2008) highlighted the importance of soil water storage change in determining both annual and seasonal water balances. Wang (2012) evaluated changes in inter-annual water storage at 12 watersheds in Illinois using the field observation of long-term groundwater and soil water and found that the impact of inter-annual water storage changes on the water supply in the BH need to be considered. Chen et al (2013) defined the difference between rainfall and storage change as effective precipitation to develop a seasonal model for construction long-term evapotranspiration.…”
Section: Du Et Al: Role Of Water Balance In An Extended Budyko Hymentioning
confidence: 99%